Formation of technical and tactical actions of taekwondo athlete of 11-12 years old - Georgy Zantaraya; Rusudan Arkaniya; Konstantin Ananchenko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: optimization of the process of teaching the technical and tactical actions of young taekwondo athlete of 11-12 years old. Material and methods: in order to conduct the experiment, two groups were completed. The experimental and control groups consisted of 12 athletes each. At the beginning and at the end of the pedagogical experiment, the method of expert evaluations was used, the elements of effective and often used in competitive fights technical and tactical actions of young taekwondo players were counted. Research methods: theoretical analysis and generalization of literary sources, pedagogical observations, method of expert assessments, determination of indicators of competitive activity of young taekwondo athlete aged 11-12, methods of mathematical statistics. Results: in the pedagogical experiment, for each athlete in the experimental group, the optimal trajectory of the shock movement was determined using the «ATAKA» computer program, in which the greatest effect of the force and speed of the impact is achieved.The introduction of an experimental training technique has allowed young taekwondo athletes to increase their competitive performance. The number of real and evaluated attacks in the study group increased by 1.9% (t = 5.13; p <0.001) and 7% (t = 10.00;p <0.001). Attack efficiency improved by 8.6% (t = 4.35; p <0.001), the interval of attacks decreased by 9.3%, the number of net victories increased by 8.2% (t = 4.11; p <0.01), and the number of warnings decreased by 8.6% (t = 2.50; p <0.05). Conclusions: the data obtained allowed us to conclude that the use of this technique using the «KORPUS» simulator and the «ATAKA» computer program in the taekwondo training system provides positive changes in technical and physical fitness in the experimental group compared to the control group.